Investigating Local Historical Figures: The Implementation of the PjBL Model to Increase Historical Literacy - Uun Lionar; Agus Mulyana; Sapriya; Murdiyah Winarti; Ridho Bayu Yefterson; Yelda Syafrina; Hendra Naldi; Yuhardi (Paramita: Historical Studies Journal, 2025)
Abstract: This study aims to analyze the implementation of the Project-Based Learning (PjBL) model by utilizing the biographies of West Sumatra's local historical figures in improving students' historical literacy in social studies learning. The main question is how implementing the PjBL model improves students' historical literacy towards local historical figures of West Sumatra? Qualitative research methods are used to understand patterns and explore data in depth on research subjects, namely social studies teachers and students in social studies subjects in several public junior high schools in Padang City. The results showed that the implementation of the PjBL model by utilizing the biographies of local historical figures of West Sumatra has encouraged the process of increasing historical literacy in students, the mastery of more historical knowledge indicates this, the development of the ability to analyze and discuss various historical sources, and the skills of students in writing history and presenting products in a creative form. This research shows that historical literacy as part of disciplinary literacy can be developed through various learning models oriented towards learners' active involvement. In addition, this research also indicates that contextualized learning materials contribute to creating meaningful learning. Abstrak: Penelitian ini bertujuan untuk menganalisis implementasi model Project Based Learning (PjBL) dengan memanfaatkan biografi tokoh sejarah lokal Sumatera Barat dalam meningkatkan literasi sejarah peserta didik pada pembelajaran IPS. Pertanyaan pokok diajukan adalah bagaimana implementasi model PjBL dalam meningkatkan literasi sejarah peserta didik terhadap tokoh sejarah lokal Sumatera Barat?. Metode penelitian kualitatif digunakan untuk memahami pola dan mengeksplorasi data secara mendalam pada subjek penelitian, yakni guru IPS dan peserta didik pada mata Pelajaran IPS di beberapa SMP Negeri di Kota Padang. Hasil penelitian menunjukkan bahwa implementasi model PjBL dengan memanfaatkan biografi tokoh sejarah lokal Sumatera Barat telah mendorong terjadinya proses peningkatan literasi sejarah pada peserta didik, hal ini ditandai dengan penguasaan pengetahuan sejarah yang semakin banyak, berkembangnya kemampuan menganalisis dan membahas berbagai sumber sejarah, dan keterampilan peserta didik dalam menulis sejarah dan menyajikan produk dalam bentuk yang kreatif. Penelitian ini menunjukkan bahwa literasi sejarah sebagai bagian dari literasi disiplin dapat dikembangkan melalui berbagai model pembelajaran yang berorientasi pada keterlibatan aktif peserta didik. Di samping itu, penelitian ini juga menunjukkan bahwa materi pembelajaran yang kontekstual juga memberikan berkontribusi dalam menciptakan pembelajaran yang bermakna.